Peningkatan Keterampilan Teknik Siswa SMK Nasional Dawarblandong melalui Pembelajaran Berbasis Proyek dengan Pendekatan Otomasi pada Alat Pertanian - Joessianto Eko Poetro; Agus Khumaidi; Imam Sutrisno; Ii Munadhif; Mochammad Rifai (Bulletin of Community Engagement, 2024)
This service aims to improve the technical skills of Dawarblan-dong National Vocational School students through project-based learning with an automation approach to agricultural equipment. The service method used is class action service. The service instruments used are observation, tests and interviews. The service subjects were 30 students of class XI Automotive Light Vehicle Engineering. Data were analyzed using descriptive statistics. The results of the service show that project-based learning with an automation approach to agricultural equipment can significantly improve the technical skills of Dawarblandong National Vocational School students. This is proven by the increase in student test scores from an average of 65.00 to 80.00 after taking part in the learning. Apart from that, the results of observations show that students become more active and creative in learning. Students are also more motivated to learn and complete projects. The results of the interviews showed that students felt happy and challenged by project-based learning with an automation approach to agricultural equipment. Project-based learning with an automation approach to agricultural tools can be an effective learning alternative for improving the technical skills of Dawarblan-dong National Vocational School students. This learning can improve students' knowledge, skills and attitudes in the field of engineering.